CORPORATE RESPONSIBILITY FOR ENVIRONMENT DAMAGE DUE TO FOREST FIRE IN RIAU PROVINCE BASED ON THE PROVINCE'S STRICT RESPONSIBILITY POLICY - Andi Maulana; Sunarno Sunarno; Khalida Ulfa (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The occurrence of forest and land fires in the regions of Riau Province has gradually occurred from year to year which has attracted a lot of attention in various circles and is very worrying, the forest fires that occur need serious handling from various parties, especially the government that has policies. One of the factors in the occurrence of forest fires is the impact of the corporations in the surrounding area itself, so the application and imposition of sanctions against related corporations in order to prevent the occurrence of forest fires in Riau Province. Approximately 300 areas in Riau Province were affected by forest fires in 2015 which were deformed by HTI (Industrial Plantation Forest). The granting of licenses to corporations operating in plantations and forests is more stringent As a form of obligation, the government authorities should immediately revoke the license to operate in the focus of a concession that is experiencing a fire. The results of this study are, in the application of the principle of strategic liability for companies to be responsible for the expansion of forests in the region of Riau Province.